EFFECT OF THYROXINE ON HATCHING AND ON POSTEMBRYONIC GROWTH IN BRACHYDANIO RERIO, CYPRINUS CARPIO, LABEO ROHITA, DIRRHINA MRIGALA AND CATLA CATLA - SAWANT, N. H.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
Studies on the effect of thyroxine on the eggs and postembryonic gÂ·rowth of Brachydanio rerio, Cyprinus carpio, Labeo rohita, Cirrhina mrigala and Catla catla have been carried out. The treatments were given in the dosages ranging from 0.025 to 0.20 mg. Lower doses of 0.025 to 0.075 mg were effective in reducing the hatching period, accelerating the yolk absorption and improving the growth of postembryonic s ages in case of all the five species. Higher doses of 0.15 to 0.20 mg were found to reduce the survival significantly in B.rerio, C. carpio, L. rohita and C.mrigala.